The use of artificial intelligence and machine learning in the management of heat transfer and cooling processes at production sites - Zhumabaeva, A. K.; Ormanbekova, A. A.; Imanbek, B. T. (Харківський національний автомобільно-дорожній універститет, 2024)
Over the past two decades, significant progress has been made in the use of machine learning methods (ML) for modeling heat transfer and heating systems. ML methods allow researchers to model highly linear and dynamic relationships between many variables, which were very complex tasks when using traditional empirical correlations.
Keywords: machine learning; artificial intelligence; heating; ventilation and air conditioning systems; 004.896